Multidrug-Resistant Uropathogens Causing Community Acquired Urinary Tract Infections among Patients Attending Health Facilities in Mwanza and Dar es Salaam, Tanzania - Vitus Silago; Nyambura Moremi; Majigo Mtebe; Erick Komba; Salim Masoud; Fauster X. Mgaya; Mariam M. Mirambo; Helmut A. Nyawale; Stephen E. Mshana; Mecky Isaac Matee (MDPI AG, 2022)
In low-income countries, the empirical treatment of urinary tract infections (UTIs) without laboratory confirmation is very common, especially in primary health facilities. This scenario often leads to unnecessary and ineffective antibiotic prescriptions, prompting the emergence and spread of antimicrobial resistance. We conducted this study to examine the antibiogram of uropathogens causing community-acquired urinary tract infections among outpatients attending selected health facilities in Tanzania. Method: This was a cross-sectional health centre-based survey conducted for a period of five months, from July to November 2021, in the Mwanza and Dar es Salaam regions in Tanzania. We enrolled consecutively a total of 1327 patients aged between 2 and 96 years with a median [IQR] age of 28 [22-39] from Dar es Salaam (n = 649) and Mwanza (n = 678). Results: Significant bacteriuria was observed in 364 (27.4% [95%CI: 25.0-29.9]) patients, from whom 412 urinary pathogens were isolated. Gram-negative bacteria contributed to 57.8% (238) of the 412 uropathogens isolated, of which 221 were Enterobacterales, and Escherichia coli was the most frequent. Staphylococcus aureus and Staphylococcus haemolyticus were the most frequently isolated among Gram-positive uropathogens (n = 156). Generally, resistance among Escherichia coli ranged from 0.7% (meropenem) to 86.0% (ampicillin) and from 0.0% (meropenem) to 75.6% (ampicillin) in other Enterobacterales. Moreover, about 45.4% (108) of Enterobacterales and 22.4% (35) of Gram-positive bacteria were multidrug resistant (MDR), p = 0.008. We observed 33 MDR patterns among Gram-negative bacteria, predominantly AMP-CIP-TCY (23/108; 21.3%), and 10 MDR patterns among Gram-positive bacteria, most commonly CIP-GEN-TCY (22/35; 62.9%). Conclusion: the presence of a high number of wide-ranging uropathogens that are multidrug resistant to a variety of antibiotics points to the need to strengthen the laboratory diagnostic systems for the regular surveillance of the antimicrobial resistance of uropathogens to guide and update empirical treatment guidelines.